2000
DOI: 10.1039/b005662f
|View full text |Cite
|
Sign up to set email alerts
|

Composition profiling of seized ecstasy tablets by Raman spectroscopy

Abstract: Raman spectroscopy with far-red excitation has been investigated as a simple and rapid technique for composition profiling of seized ecstasy (MDMA, N-methyl-3,4-methylenedioxyamphetamine) tablets. The spectra obtained are rich in vibrational bands and allow the active drug and excipient used to bulk the tablets to be identified. Relative band heights can be used to determine drug/excipient ratios and the degree of hydration of the drug while the fact that 50 tablets per hour can be analysed allows large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 9 publications
0
85
0
3
Order By: Relevance
“…It was demonstrated that the eigenvalue-based criteria for choosing principal components was ineffective for these Raman Chemical Images, and the author remarked that the basic postulates of PCA could pose a significant problem when applied to Raman mapping spectra. For NIR mapping spectra, interpretation of PCA proved difficult; problems were associated with associating pure component spectra Bell et al [51] , [55], [56] and [57] published findings on the development of quantitative analytical methods for Raman analysis of solid dosage forms. In one paper, this research team reported results on Raman mapping of seized ecstasy tablets [51].…”
Section: Tablet Characterisationmentioning
confidence: 99%
“…It was demonstrated that the eigenvalue-based criteria for choosing principal components was ineffective for these Raman Chemical Images, and the author remarked that the basic postulates of PCA could pose a significant problem when applied to Raman mapping spectra. For NIR mapping spectra, interpretation of PCA proved difficult; problems were associated with associating pure component spectra Bell et al [51] , [55], [56] and [57] published findings on the development of quantitative analytical methods for Raman analysis of solid dosage forms. In one paper, this research team reported results on Raman mapping of seized ecstasy tablets [51].…”
Section: Tablet Characterisationmentioning
confidence: 99%
“…Although there are some reported studies on the Raman analysis of amphetamine-like compounds [14][15][16][17][18][19][20][21], these experiments have only focused on particular regions of the vibrational spectra.…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed, rather than explicitly demonstrated, that the large surface area from which the signal was collected ensured that this spectrum was representative of the average composition of the sample. 1,3 Although this rotating tablet arrangement is widely used, it is typically only applied in situations where manually loading tablets one at a time is acceptable because it is difficult to combine sample rotation with automated high-throughput analysis of large numbers of tablets. In the work here, the approach taken was to mount sets of tablets on a motorized sample stage and to record data from a grid of points on each tablet (and from each tablet in the sample holder) by stepping the stage in the x and y directions.…”
Section: Introductionmentioning
confidence: 99%